Does disability explain state-level differences in the quality of Medicare beneficiary hospital inpatient care? - Brian S. Armour; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2007)
Almost 20 percent of the total U.S. population and 42 percent of the population over the age of sixty-six are disabled. Research has shown that the presence of a disability can crowd out treatment for medical conditions not necessarily related to the disability and that states that are disproportionately African-American have a lower quality of hospital care. This paper uses quality of care data from the Centers for Medicare and Medicaid Services (CMS) to determine whether disability also explains state-level differences in quality of hospital care. The quality of Medicare beneficiary hospital care was measured using process measures for several medical conditions, including acute myocardial infarction, heart failure, stroke, and pneumonia, that are the leading causes of mortality. We use nonlinear least squares to assess the association between Medicare beneficiary quality of care and state- and medical system-level characteristics. The result for the key variable of interest - disability - reveals that a 1 percent increase in a state's disability rate leads to a 1 percentage point reduction in the score of the state's quality of hospital care. Without explicitly incorporating strategies to eliminate disparities in care incurred by people with disabilities, CMS may not adequately promote the goal of delivering the highest quality of care to all Medicare beneficiaries.
Keywords: I11; 330; disability; process measures; Medicare